Screening antimicrobial activity of tropical edible medicinal plant extracts against five standard microorganisms for natural food preservative - Rukayadi, Yaya; Lau, K. Y.; Zainin, N. S.; Zakaria, Mohamed (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Edible medicinal plants are often used in the treatment of various ailments and spice in traditional food preparation. In this study, 45 of tropical edible medicinal plants extracts from Indonesia, Malaysia, and Thailand were screened for their antimicrobial activity against five standard microorganisms for food preservative namely Aspergillus niger, Candida albicans, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The methanol extracts of Piper nigrum L. seed, Piper cubeba L. seed, and the root of Ligusticum acutilobum Siebold and Zucc. showed antimicrobial activity against five species of standard microorganisms. Among them, P. cubeba L. extract demonstrated the most susceptible against all tested microorganisms. Minimal inhibitory concentration (MIC) and minimal bactericidal or fungicidal concentration (MBC or MFC) were performed by the broth microdilution techniques as described by the Clinical and Laboratory Standard Institute. MIC values of P. cubeba L. extract to A. niger, C. albicans, E. coli, P. aeruginosa and S. aureus were 12.8, 1.6, 3.2, 6.4, and 1.6 mg/ml, respectively. P. cubeba extract killed A. niger, C. albicans, E. coli, P. aeruginosa and S. aureus with MBC values of 25.6, 3.2, 6.4, 12.8, and 3.2 mg/ml, respectively. The potent antimicrobial activity of P. cubeba L. extract may support its use for natural food preservative.